EVALUASI ISI AWAL GAS DI TEMPAT DAN ANALISIS DECLINE CURVE PADA RESERVOIR YS - Yogie Seto S.W; Onnie Ridaliani; Lestari Lestari (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
YS reservoir has data of gas initial in place (GIIP) with a volumetric method of 3,476 Bscf. Because of improvement of data, GIIP can be evaluated using material balance method. Then the production of wet gas will be forcasted with plateu rate of 40 Mscf/d. The PVT data that needs to be calculated in this study is the gas and water compressibility factor and the formation volume factor each year. In determining the type of drive mechanism, a plot of P / Z versus cumulative gas production is carried out, from the analysis, the type of drive mechanism is water drive, it is necessary to calculate the water influx, the method used is the Van Everdengen-Hurst method. After all the required parameters are available, the calculation of the initial gas in place will be calculated, the method used is the material balance method and the straight line material balance method. The results of the initial gas in place calculation using the material balance and straight line material balance methods are 3,430 Bscf and 3,428 Bscf. If the results of the material balance method and the straight line material balance method are compared with available GIIP volumetric method data, the percent difference is 1,32% and 1,37%. It can be said that GIIP result using the material balance method and the straight line material balance method is accurate because after being evaluated using volumetric method, it only has a small percentage difference. Then from calculation, recovery factor are 67,43% using gas initial in place of straight line material balance method. With remaining reserve of 16,532 MMscf, the time of production plateu with 40 Mscf/d is 12,40 months.